Analysis of the dose-dependent stage-specific in vitro efficacy of a multi-stage malaria vaccine candidate cocktail. (December 2016) - Boes, Alexander; Spiegel, Holger; Kastilan, Robin; Bethke, Susanne; Voepel, Nadja; Chudobová, Ivana; Bolscher, Judith; Dechering, Koen; Fendel, Rolf; Buyel, Johannes; Reimann, Andreas; Schillberg, Stefan; et al.
Abstract Background The high incidence and mortality rate of malaria remains a serious burden for many developing countries, and a vaccine that induces durable and highly effective immune responses is, therefore, desirable. An earlier analysis of the stage-specific in vitro efficacy of a malaria vaccine candidate cocktail (VAMAX) considered the general properties of complex multi-component, multi-stage combination vaccines in rabbit immunization experiments using a hyper-immunization protocol featuring six consecutive boosts and a strong, lipopolysaccharide-based adjuvant. This follow-up study investigates the effect of antigen dose on the in vitro efficacy of the malaria vaccine cocktail using a conventional vaccination scheme (one prime and two boosts) and a human-compatible adjuvant (Alhydrogel® ). Results IgG purified from rabbits immunized with 0.1, 1, 10 or 50 µg doses of the VAMAX vaccine candidate cocktail was analysed for total IgG and antigen-cocktail-specific titers. An increase in cocktail-specific titers was observed between 0.1 and 1 µg and between 10 and 50 µg, whereas no significant difference in titers was observed between 1 and 10 µg. Antigen component-specific antibody titers and stage-specific in vitro efficacy assays were performed with pooled IgG from animals immunized with 1 and 50 µg of the VAMAX cocktail. Here, the component-specific antibody levels showed clear dose dependency whereas the determined stage-specific in vitro IC50 values (as a correlate of efficacy) were only dependent on the titer amounts of stage-specific antibodies. Conclusions The stage-specific in vitro efficacy of the VAMAX cocktail strongly correlates with the corresponding antigen-specific titers, which for their part depend on the antigen dose, but there is no indication that the dose has an effect on the in vitro efficacy of the induced antibodies. A comparison of these results with those obtained in the previous hyper-immunization study (where higher levels of antigen-specific IgG were observed) suggests that there is a significant need to induce an immune response matching efficacy requirements, especially for aPf AMA1-based blood stage vaccine, by using higher doses, better adjuvants and/or better formulations.